Attitudes toward risk among small farmers in southern Huila - Arcia, G (International Center for Tropical Agriculture, 1980)
Timely evaluation of new technology performance is extremely important for international research centers. As part of the evaluation efforts of new bean technology currently in process at CIAT, a mathematical model of the bean farm is being implemented. One of its features is the incorporation of risk aversion on the farmer`s objective function. The present paper deals with the methods and results of the elicitation of risk aversion among farmers in S. Huila, Colombia. The results seem to indicate that farmers are generaly risk averse when faced with uncertain options. Furthermore, their degree of risk aversion is significantly inverse to subsistence security. Regressions of socioeconomic factors on risk aversion indicate that there is room for risk aversion reduction through policy instruments. (AS)